2021
DOI: 10.12786/bn.2021.14.e11
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Epidemiological Trends and Rehabilitation Usage in Neurological Diseases in Korea: Stroke

Abstract: Stroke survivors with disabilities have increased in Korea as the population has aged. Early stroke rehabilitation is known to be an essential therapy in gaining functional independence and preventing complications. Recent research on the rehabilitation usage of stroke patients was reviewed in this manuscript. For the past 15 years, it was found that comprehensive rehabilitation assessments have been performed faster in more stroke patients, and intensive inpatient stroke rehabilitation has been applied to mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Considering the larger decrease in disabilities by a stroke (50.3%) than that by any cause (40.9%), factors alleviating the severity and sequelae of the disease may have contributed to better health outcomes in 2010–2012 (KNHANES V) and beyond. These factors include the improvement of a healthcare system for hyper-acute management and the introduction of the delivery system for early and continuous rehabilitation [ 20 ]. The innovations in stroke treatment and the introduction of intensive stroke units may have affected the decrease in the incidence of disabilities in community-dwelling stroke survivors [ 21 22 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the larger decrease in disabilities by a stroke (50.3%) than that by any cause (40.9%), factors alleviating the severity and sequelae of the disease may have contributed to better health outcomes in 2010–2012 (KNHANES V) and beyond. These factors include the improvement of a healthcare system for hyper-acute management and the introduction of the delivery system for early and continuous rehabilitation [ 20 ]. The innovations in stroke treatment and the introduction of intensive stroke units may have affected the decrease in the incidence of disabilities in community-dwelling stroke survivors [ 21 22 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RCCVC project in Korea was launched in 2008 with the aim to manage acute stroke patients within 3 hours. The inexpensive and efficient rehabilitation services covered by National Health Insurance system in Korea may also have affected the reduction of the incidence of disabilities in stroke survivors [ 20 25 ]. A previous study reported that transfer time to the rehabilitation department after onset decreased from 44 days in 2007 to 30 days in 2011 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, the incidence of stroke is gradually increasing with the aging of the population [3]. Many stroke survivors return to the community with functional impairments after receiving acute treatment and rehabilitation [3,4]. Even after discharge, informal caregivers provide daily living support to stroke survivors according to their level of functional independence [5,6].…”
Section: Introductionmentioning
confidence: 99%